Pengembangan Modul Fashion Fotografi Pada Prodi D3 Tata Busana Jurusan Pendidikan Kesejahteraan Keluarga Fakultas Teknik Universitas Negeri Makassar - Nawawi, Faizah; Muhammad Yahya; St. Aisyah (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2024)
This research aims to determine the stages of development of the Fashion Photography Learning Module learning module, find out the Fashion Photography Learning Module is valid according to the validation results of material and media experts, find out the Fashion Photography learning module is practical to apply and find out the Fashion Photography learning module is effective for students in the Fashion Design Study Program. Department of Family Welfare Education, Faculty of Engineering, Makassar State University. This research is development research (Research and Development), which uses the ADDIE development model. The research subjects in this study were students of the Fashion Design Study Program, Family Welfare Education Department, Faculty of Engineering, Makassar State University who had programmed the Fashion Photography course. Data collection instruments were carried out through validation test sheets, practicality questionnaires and effectiveness questionnaires. The data analysis technique used is descriptive analysis. The research results show that the Fashion Photography learning module has a validity percentage value with 2 experts validating the media and material with material validation results of 92.17% in the very valid category, while media expert validation results are 92%. The results of one-on-one trials with 5 research subjects were 98%, the results of small group trials with 15 research subjects were 88% with the Very Practical category. At the large group trial stage to measure the effectiveness of the Fashion Photography learning module, there were 30 research subjects with results of 90.31% in the Very Good category. The conclusion from the results of the validation research, practicality and effectiveness is that the Fashion Photography Learning Module is very suitable for use by D3 students of the PKK FT UNM Study Program in the Fashion Photography course.